Leaf area, air temperature, and yield in monocropped and intercropped beans and maize - Portes, Tomás de Aquino; Carvalho, José Ruy Porto de (Pesquisa Agropecuaria Brasileira, 2014)
Two bush and two climbing bean (Phaseolus vulgaris L.) cultivars were sown in monocrop and intercrop with two maize (Zea mays L.) cultivars, one short (Piranão and one tall (Ag-259). Until 25-35 days after emergence there was no difference in leaf area index (LAI). between the two crop systems. After this period, LAI values for Ag-259 were smaller in the intercrop than in the monocrop, but Piranão showed no difference. Thirty days after emergence, maize LAI became higher than in monocrop, and three to five times superior to those of beans. The climbing cultivars were less efficient than the bush ones. At tasseling, the maize intercepted nearly 80% of the light. Mean, maximum and minimum temperatures obtained inside the canopy were not different between intercrop and monocrop. Except for the bean cultivar California Small White, all bean yields in intercrop were lower than 50% of the monocrop yields. Maize yields were not significantly reduced.